2019
DOI: 10.1371/journal.ppat.1008037
|View full text |Cite
|
Sign up to set email alerts
|

Host signaling and EGR1 transcriptional control of human cytomegalovirus replication and latency

Abstract: Sustained phosphotinositide3-kinase (PI3K) signaling is critical to the maintenance of alpha and beta herpesvirus latency. We have previously shown that the beta-herpesvirus, human cytomegalovirus (CMV), regulates epidermal growth factor receptor (EGFR), upstream of PI3K, to control states of latency and reactivation. How signaling downstream of EGFR is regulated and how this impacts CMV infection and latency is not fully understood. We demonstrate that CMV downregulates EGFR early in the productive infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 81 publications
(145 reference statements)
9
91
2
1
Order By: Relevance
“…This protein has been reported to have an antagonistic relationship with another viral protein, UL135 [36]. During latency, UL138 regulates epidermal growth factor receptor (EGFR) localization to ensure Pi3K signaling is active in the cell which is hypothesized to help maintain latency via the Egr-1 transcription factor [37] an event also targeted by a virally encoded miRNA [38]. Consistent with this is the observation that Pi3K inhibitors trigger HCMV reactivation in vitro suggesting that this pathway actively supports latency [37].…”
Section: Multiple Cell Signaling Pathways Have Been Implicated In Hcmmentioning
confidence: 81%
See 1 more Smart Citation
“…This protein has been reported to have an antagonistic relationship with another viral protein, UL135 [36]. During latency, UL138 regulates epidermal growth factor receptor (EGFR) localization to ensure Pi3K signaling is active in the cell which is hypothesized to help maintain latency via the Egr-1 transcription factor [37] an event also targeted by a virally encoded miRNA [38]. Consistent with this is the observation that Pi3K inhibitors trigger HCMV reactivation in vitro suggesting that this pathway actively supports latency [37].…”
Section: Multiple Cell Signaling Pathways Have Been Implicated In Hcmmentioning
confidence: 81%
“…During latency, UL138 regulates epidermal growth factor receptor (EGFR) localization to ensure Pi3K signaling is active in the cell which is hypothesized to help maintain latency via the Egr-1 transcription factor [37] an event also targeted by a virally encoded miRNA [38]. Consistent with this is the observation that Pi3K inhibitors trigger HCMV reactivation in vitro suggesting that this pathway actively supports latency [37]. Interestingly, work from the Trono laboratory demonstrated that chloroquine also drove HCMV reactivation by modulating the activity of the transcriptional repressor, TRIM28/KAP1 [39].…”
Section: Multiple Cell Signaling Pathways Have Been Implicated In Hcmmentioning
confidence: 99%
“…Initial PI3K/AKT activation is required for efficient viral entry as well as optimal replication in fibroblasts and establishment of latency in monocytes [156,158,[160][161][162][163]. However, at later times during infection inhibition of EGFR or PI3K seems to favour viral replication and reactivation from latency suggesting a negative regulatory role at this point [164][165][166][167]. Besides PI3K/AKT signalling, various other kinase pathways are known to be activated very early during HCMV infection.…”
Section: Transcriptional Control Of the Major Ie Genementioning
confidence: 99%
“…While iP1 and iP2 promoters are necessary for efficient reactivation, the factors regulating their activity are unknown. Reactivation is induced by differentiation of monocytes into macrophages, a process that is mimicked in experimental latency models by treating latently infected cells with phorbol esters (e.g., TPA) (10) or LY294002 (20), a chemical inhibitor of the PI3K/mTOR pathway. A literature review found that phorbol esters, LY294002, and monocyte differentiation all activate FOXO family of transcription factors (21).…”
Section: Resultsmentioning
confidence: 99%